Powerpoint Assisted Problem Posing versus STAD Model: A Comparison Study in Improving Mathematical Connection Ability - Sikana, Aria Mana; Paridjo, Paridjo; Utami, Wikan Budi (Jurnal Pendidikan Progresif, 2018)
Powerpoint assisted problem posing versus STAD model: A comparison study in improving mathematical connection ability. Objectives: The purpose of this study were to determine the differences and the effectivity between Powerpoint Assisted Problem Posing and Student Team Achievement Divisions (STAD) on mathematical connection ability. Methods: The population of this study were 289 students of SMPN 1 Talang year of 2017/2018 class VII semester II. Data of mathematical connection ability were collected by using documentation, tests and observations. Findings: There were significant differences in mathematical connection ability between Powerpoint Assisted Problem Posing and the STAD model (t calc=5.287 > ttable=1.960). Conclusions: Powerpoint Assisted Problem Posing Model is more effective than STAD model (t calc=5.287 > ttable=1.645 and sig. 0.000) in improving mathematical connection ability. Keyword: Powerpoint-assisted problem posing, STAD model, mathematical connection ability. DOI: http://dx.doi.org/10.23960/jpp.v8.i2.201810